2014
DOI: 10.1021/jm501203v
|View full text |Cite
|
Sign up to set email alerts
|

Development of (E)-2-((1,4-Dimethylpiperazin-2-ylidene)amino)-5-nitro-N-phenylbenzamide, ML336: Novel 2-Amidinophenylbenzamides as Potent Inhibitors of Venezuelan Equine Encephalitis Virus

Abstract: Venezuelan equine encephalitis virus (VEEV) is an emerging pathogenic alphavirus that can cause significant disease in humans. Given the absence of therapeutic options available and the significance of VEEV as a weaponized agent, an optimization effort was initiated around a quinazolinone screening hit 1 with promising cellular antiviral activity (EC50 = 0.8 μM), limited cytotoxic liability (CC50 > 50 μM), and modest in vitro efficacy in reducing viral progeny (63-fold at 5 μM). Scaffold optimization revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 29 publications
3
58
0
Order By: Relevance
“…In one study, the identified CID15997213 compound demonstrated a strong inhibitory effect on VEEV replication in vitro and in a small animal model via its targeting of the nsP2 protein and ultimately viral RNA replication (14). Some other quinazolinone-derived molecules also exhibited antiviral activity against VEEV (15,16). For example, compound ML336 inhibited several VEEV strains in the nanomolar range in vitro and also protected mice from a lethal VEEV infection.…”
mentioning
confidence: 99%
“…In one study, the identified CID15997213 compound demonstrated a strong inhibitory effect on VEEV replication in vitro and in a small animal model via its targeting of the nsP2 protein and ultimately viral RNA replication (14). Some other quinazolinone-derived molecules also exhibited antiviral activity against VEEV (15,16). For example, compound ML336 inhibited several VEEV strains in the nanomolar range in vitro and also protected mice from a lethal VEEV infection.…”
mentioning
confidence: 99%
“…VEEV is an RNA virus that causes encephalitis in humans and equids, and effective therapeutics for the disease have not yet been developed. We screened a library of 348,000 small-molecule compounds with a cell-based assay that measured the protection of cells from VEEV-induced cytopathic effect (strain TC-83) and discovered five active compounds (hits) with 50% effective concentrations (EC 50 s) that were better than 15 M. One of these hits and the resulting optimized lead, ML336, turned out to be a DAA that inhibits viral RNA synthesis by targeting the amino terminal domains of viral nonstructural proteins 2 and 4 (8,9).…”
mentioning
confidence: 99%
“…The utility of this method was further demonstrated for each of the two accessible guanidine structural classes. Plasma stability is one optimization parameter in our antiviral medicinal chemistry program . Mouse plasma stability of around 65 % has been generally observed for a series of benzamidines, and we questioned the stability of the benzamidine functionality towards enzymatic hydrolysis in vivo.…”
Section: Resultsmentioning
confidence: 99%